2018
DOI: 10.1016/j.ajpath.2018.07.027
|View full text |Cite
|
Sign up to set email alerts
|

Placental Adaptation to Early-Onset Hypoxic Pregnancy and Mitochondria-Targeted Antioxidant Therapy in a Rodent Model

Abstract: The placenta responds to adverse environmental conditions by adapting its capacity for substrate transfer to maintain fetal growth and development. Early-onset hypoxia effects on placental morphology and activation of the unfolded protein response (UPR) were determined using an established rat model in which fetal growth restriction is minimized. We further established whether maternal treatment with a mitochondria-targeted antioxidant (MitoQ) confers protection during hypoxic pregnancy. Wistar dams were expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
88
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(98 citation statements)
references
References 90 publications
9
88
1
Order By: Relevance
“…), further studies are needed to investigate new tools, such as the mitochondria‐targeted antioxidant MitoQ (Nuzzo et al . ), for manipulating ROS levels as a way to improve pregnancy outcomes for women with PCOS.…”
Section: Discussionmentioning
confidence: 99%
“…), further studies are needed to investigate new tools, such as the mitochondria‐targeted antioxidant MitoQ (Nuzzo et al . ), for manipulating ROS levels as a way to improve pregnancy outcomes for women with PCOS.…”
Section: Discussionmentioning
confidence: 99%
“…The contribution of O 2 consumption by non-OXPHOS-related processes (such as steroid and nitric oxide production) could also be explored in future work using ETS inhibitors (e.g., rotenone and antimycin). Indeed, studies using the mitochondrial-targeted antioxidant MitoQ suggest non-OXPHOS processes may have a significant effect on substrate exchange, placental secretions, and fetal growth in hypoxic rat dams (17,43).…”
Section: Discussionmentioning
confidence: 99%
“…In humans, hypoxia is the main cause of fetal growth restriction at high altitude and is a common feature of pregnancy complications at sea level (13). In pregnant rodents and guinea pigs, inhalation hypoxia adapts placental morphology and nutrient transport to the fetus dependent upon the degree, timing, and length of O 2 restriction ( [14][15][16][17][18][19]. Changes in placental mitochondrial function are also seen in compromised human pregnancies (3) and in nutritionally induced fetal growth restriction in rodents, in association with changes in mitochondrial function and biogenesis (20,21).…”
mentioning
confidence: 99%
“…These include an increase in placental weight, vascularization and capillary surface area for exchange, which depend on the severity and duration of the hypoxic insult and may not necessarily lead to significant effects on fetal body weight. [73][74][75][76][77] In this context, studies in rodent pregnancy by our own laboratory have shown that late-onset hypoxia for the last third of gestation leads to significant FGR. 78 In contrast, earlyonset hypoxic pregnancy increases placental weight, cushioning the adverse effects on fetal development, leading to maintained birth weight.…”
Section: Effects Of Maternal Hypoxia On the Fetoplacental Unitmentioning
confidence: 99%